Is it who you know or what you know? Evidence from ipo allocations and mutual fund performance - Hwang, Chuan-Yang (2019)
Mutual fund managers with degrees from elite universities tend to outperform their counterparts from less elite universities. We show that the better performance of elite graduates is generated from their better connections with underwriters that facilitate allocations to underpriced initial public offerings (IPOs). Indeed, we find that the funds outperform only in months when they are connected to underwriters issuing IPOs. A strategy of buying mutual funds in months when they are connected to underwriters scheduled to issue IPOs generates significant abnormal returns, as high as 4.08% per annum in hot markets.